Pengaruh Kecanduan Media Sosial Tiktok Terhadap Minat Belajar Matematika Siswa Kelas III SD NU Sleman - Nisa Nurhayati; Wahyu Purwaningsih (Journal of Contemporary Issues in Primary Education, 2026)
Excessive use of tiktok has the potential to cause addiction and affect various aspects of student development, including learning interest. This study aims to analyze the effect of TikTok social media addiction on the interest in learning mathematics of third-grade students at SD NU Sleman. The method used is quantitative ex-post facto with a total of 68 students determined through purposive sampling technique. Data were collected using a questionnaire and analyzed using simple linear regression analysis techniques and coefficient of determination (R2) analysis. Hypothesis testing shows that TikTok social media addiction has a significant effect on the variable of interest in learning mathematics. The coefficient of determination obtained is Y = 33.971 + 0.237, which means that for every one unit increase in variable X, the interest in learning mathematics (Y) will increase by (0.237) units with a constant value of 33.975. The coefficient of determination obtained is 0.174 (17.4%), meaning that TikTok addiction has a 17.4% contribution to interest in learning mathematics and the remaining 82.6% is influenced by other factors explained by other models outside the topic of this study.